On 70th Anniversary of the First Issue of Oftalmologicheskii Zhurnal (Journal of Ophthalmology (Ukraine)) (Ukrainian Journal of Ophthalmology, 2026)
In June 2016, it will be 70 years from the first  issue of the journal Oftalmologicheskii Zhurnal which was founded by academician Vladimir P. Filatov.